2008
DOI: 10.1097/aog.0b013e31818da09b
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Blood Pressure Changes Measured From Before to After Pregnancy Relative to Nonparous Women

Abstract: Objective To prospectively examine whether blood pressure changes persist after pregnancy among women of reproductive age. Methods Prospective, population-based, observational cohort of 2,304 (1,167 black, 1,137 white) women (aged 18–30) who were free of hypertension at baseline (1985–86) and reexamined up to six times at 2, 5, 7, 10, or 20 years later (2005–2006). We obtained standardized blood pressure measurements before and after pregnancies, and categorized women into time-dependent groups by the cumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 32 publications
1
54
1
1
Order By: Relevance
“…During the Year 20, 25, and 30 study visits, BP was recorded using a standard automated BP measurement monitor (Omron model HEM907XL; Omron Healthcare, Inc, Lake Forest, IL). To ensure comparability between the 2 methods, BP measurements at the Year 20 and 25 study visits were calibrated to random‐0 sphygmomanometer values based on simultaneous readings from both devices using a Y connector on a subset (n=906) of CARDIA participants 13. At all study visits, each participant's arm circumference was measured at the midpoint between the acromion and olecranon of the right arm to determine the appropriate cuff size.…”
Section: Methodsmentioning
confidence: 99%
“…During the Year 20, 25, and 30 study visits, BP was recorded using a standard automated BP measurement monitor (Omron model HEM907XL; Omron Healthcare, Inc, Lake Forest, IL). To ensure comparability between the 2 methods, BP measurements at the Year 20 and 25 study visits were calibrated to random‐0 sphygmomanometer values based on simultaneous readings from both devices using a Y connector on a subset (n=906) of CARDIA participants 13. At all study visits, each participant's arm circumference was measured at the midpoint between the acromion and olecranon of the right arm to determine the appropriate cuff size.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study in humans found that long-term maternal blood pressure was Ϸ2 mm Hg lower in parous women. 27 It was suggested that, rather than an effect of pregnancy, per se, human pregnancy may reflect a subset of women with better cardiovascular function. Evidence suggests that women who experienced complicated pregnancies were more likely to develop chronic hypertension in later life.…”
Section: Discussionmentioning
confidence: 99%
“…It may result in permanent and not just temporary detrimental effects on the body and promote weight gain, insulin resistance and dyslipidemia in later life [8,9]. Hemodynamic adaptations during pregnancy include increases in cardiac output and blood volume and decreases in perfusion pressure and total systemic vascular resistance [4]. Several studies have considered the association between parity and the prevalence of hypertension in later life and results were conflicting [3,4,10,11].…”
Section: Introductionmentioning
confidence: 98%
“…Blood pressure is affected by a number of traditional cardiovascular risk factors such as age, family history and BMI, but also those parameters related to reproductive history may play a role in hypertension development [3]. Pregnancy produces marked alterations in vascular physiology [4][5][6] and may be considered as a temporary dip into the metabolic syndrome [7]. It may result in permanent and not just temporary detrimental effects on the body and promote weight gain, insulin resistance and dyslipidemia in later life [8,9].…”
Section: Introductionmentioning
confidence: 99%